An Improved Peak Sidelobe Reduction Method for Subarrayed Beam Scanning. (9th July 2015) - Hu, Hang; Luan, Xuepeng; Zhang, Guanglei; Song, Ke; Liu, Weihui; Mou, Chenghu
Abstract : This paper focused on PSL (peak sidelobe level) reduction for subarrayed beam scanning in phased array radars. The desired GSP (Gaussian Subarray Patterns) are achieved by creating a subarray weighting network. The GSP-based method could reduce PSL of array pattern; compared with the method based on the desired subarray pattern which is defined by ideal space-domain filter, the PSL reduction performance is improved remarkably. Further, based on the concept adopting superelement patterns to approximately express original subarray patterns, the simplified GSP-based method is proposed. So the dimension of each matrix required for creating the weighting network, which was originally the same as the element number, could be reduced to the same as the subarray number. Consequently, we achieve remarkable reduction of the computation burden; simultaneously, the PSL mitigation performance is degraded slightly. Simulation results demonstrate the validity of the introduced methods.